Coronary artery bypass grafting for coronary artery anomalies in infants and young children. (4th May 2022) - Hohri, Yu; Yamagishi, Masaaki; Maeda, Yoshinobu; Asada, Satoshi; Hongu, Hisayuki; Numata, Satoshi; Yaku, Hitoshi
Abstract: OBJECTIVES: Coronary artery bypass grafting (CABG) has been reported for coronary artery diseases in patients with Kawasaki disease and coronary artery complications after arterial switch operations for transposition of the great arteries. However, only a few studies have explored this modality for congenital coronary artery anomalies. As congenital coronary artery anomalies, particularly left coronary artery atresia and stenosis, are one of the reasons for sudden death, coronary revascularization is often required in infants and young children. Therefore, we aimed to investigate the outcome of CABG for such anomalies in infants and young children. METHODS: From 2014 to 2018, 3 infants and 2 children (median age: 10 months; range: 6–40 months) with coronary artery anomalies underwent CABG at our hospital. The indications for the procedure included left main coronary artery atresia and stenosis in 2 and 3 patients, respectively. Graft patency was evaluated postoperatively by contrast-enhanced computed tomography or coronary angiography, and postoperative outcomes (including death and cardiac events) were assessed during the follow-up period. RESULTS: No 30-day or in-hospital mortalities were noted. Postoperative examinations revealed patent grafts in all patients. They were discharged without any cardiac complications. Regarding the outcomes at the follow-up period, the graft patency rate was 80.0% (4/5 grafts), with no deaths or cardiac events. CONCLUSIONS: CABG is a useful strategy for coronary revascularization in infants and young children with coronary artery anomalies. Although the mid-term outcomes and patency are satisfactory, careful follow-up is necessary because the long-term outcomes remain unknown. Abstract : Previous studies have shown that coronary artery bypass grafting (CABG) can be considered a valuable strategy for coronary revascularization in patients with Kawasaki disease [1, 2] and in those with coronary complications after an arterial switch operation for transposition of the great arteries [3, 4].